Introductory Business Learning Based on Actual Economic Issues as an Effort to Improve the Business Literacy of Accounting Education Students - Thohiri, Roza; Fazillah, Jihan; Nasution, Syakirah Shalihah Nur Azzahra; Andriarsyah, Nabilla Putri; Adawiyah, Aisyah Tul; Nisa, Khairun; Patrisia, Eflin (Journal of Educational Sciences, 2026)
This study investigates the effectiveness of introductory business learning based on current economic issues in improving business literacy among accounting education students. The background of this research lies in the need for more relevant and contextual learning strategies that align with real-world economic developments. The study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group model. A total of 41 students were divided into experimental and control groups. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using normality and homogeneity tests, independent sample t-test, normalized gain (N-Gain), and effect size analysis with the Statistical Package for the Social Sciences (SPSS). The results revealed a significant difference between the experimental and control groups, with a significance value of less than 0.05. The N-Gain score of the experimental group was categorized as moderate to high, and the effect size indicated a strong impact. These findings suggest that learning based on current economic issues is effective in enhancing students’ business literacy. Therefore, this approach is recommended as an innovative and relevant strategy in economic education.